Pulsed field ablation as the first choice regarding oesophageal safety for atrial fibrillation ablation?. (19th May 2022) - Katic, J; Sikiric, I; Lisica, L; Zaja, I; Puljiz, Z; Jurisic, Z; Breskovic, T; Anic, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The occurrence of endoscopy-detected oesophageal lesions has been reported in patients with atrial fibrillation (AF) after thermal-based pulmonary vein isolation (PVI) with even higher risk in patients undergoing ablation of the left atrial posterior wall (LAPW) (1). The main mechanism of oesophageal injury is thermal, resulting in oesophageal dysmotility, ulceration, perforation, or left atrio-oesophageal fistula formation, which are rare but life-threatening sequelae. Pulsed‐field ablation (PFA) is a non‐thermal ablation technology that uses high amplitude pulsed electrical fields to ablate tissues through cell membrane disruption (2). Precommercial experience with PFA reported no injury to the oesophagus for both PVI and LAPW ablation (3). Purpose: To assess oesophageal safety in AF patients treated with three different PFA platforms. Methods: In this single-centre experience we retrospectively analysed a total of 72 upper gastrointestinal (GI) endoscopies performed by a certified gastroenterologist one day after left atrial PFA. GI analysis focused on detection of oesophageal lesions nearest the left atrium and evidence of gastric hypomotility. PVI was performed using focal or single shot PFA catheters. Focal PFA catheters achieved PVI using the wide antral circumferential ablation (WACA) technique. LAPW ablation was performed exclusively by using single shot PFA devices. Results: The patient characteristics were summarized in Table 1. Focal PFA catheters were used in 78% of patients. Post-procedure endoscopies revealed no mucosal lesions in any patient. Gastroparesis and perioesophageal vagal nerve injury were not found (Table 2). Conclusion: PFA, whether applied by single shot devices or focal catheters, seems to be a safe ablation option with respect to oesophageal injury resulting from PVI and LAPW ablation in paroxysmal and persistent AF patients. Irrespective of catheter design, PFA configuration (monopolar versus bipolar, maximum output), or LA lesion set, we found absolute GI safety of PFA as class effect.